PERLINDUNGAN HUKUM PERDATA DALAM PENANGANAN PENEMBAKAN PESAWAT SIPIL: STUDI KASUS DAN IMPLIKASI HUKUM - Abu, Supri; Sudarto; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
This study aims to analyze civil legal protection in handling civil aircraft shootings and the settlement of civil legal disputes between the state, airlines, and victims, both based on international and national law. Civil aircraft shooting cases raise legal complexities that require effective protection for victims and fair dispute resolution. This study uses a normative juridical legal research method with a statute approach, conceptual approach, and case approach. The results of the study indicate that although there are international regulations such as the 1944 Chicago Convention and the 1999 Montreal Convention, as well as Law Number 1 of 2009 concerning Aviation in Indonesia, the implementation of legal protection still faces challenges, especially in the context of jurisdiction and political obstacles. Settlement of civil legal disputes in civil aircraft shooting cases can be done through international litigation, arbitration, mediation and settlement through insurance and compensation funds. This study recommends strengthening regulations, improving dispute resolution mechanisms, and increasing coordination between national and international laws to create better legal protection for victims.